An Intervention to Promote Breast Milk Production in Mothers of Preterm Infants. (May 2016) - Héon, Marjolaine; Goulet, Céline; Garofalo, Carole; Nuyt, Anne Monique; Levy, Emile
A pilot study was conducted to estimate the effects of a breast milk expression education and support intervention on breast milk production outcomes in mothers of very and extremely preterm infants. Forty mothers of hospitalized preterm infants (<30 weeks of gestation) were randomized to the experimental intervention or standard care for 6 weeks. Duration and frequency of breast milk expressions and volume of expressed breast milk were measured daily. Samples of breast milk were collected thrice during the study and analyzed for their lipid concentration. Mothers in the experimental group had a statistically significant higher duration of breast milk expression in min/day ( p = .043). Differences observed between the two groups regarding the frequency of breast milk expression, volume of breast milk, and lipid concentration were not statistically significant. Results suggest that the experimental intervention may promote breast milk production in mothers of very and extremely preterm infants.